Principal component analysis on morphological traits in juvenile stage arabica coffee - Teixeira, Alexsandro Lara; Gonçalves, Flávia Maria Avelar; Rezende, Juliana Costa de; Rocha, Rodrigo Barros; Pereira, Antonio Alves (Coffee Science - ISSN 1984-3909, 2013)
In plant breeding and selection, it is necessary to evaluate a great number of traits that are naturally associated. Thus, the use of multivariate analysis, such as Principal Component Analysis, can assist data interpretation. The aim of this study was to identify which morphological traits are of greatest importance to discriminate juvenile Coffea arabica genotypes. Cultivars, hybrids and some wild genotypes were evaluated from a coffee genebank maintained by the Empresa de Pesquisa Agropecuária de Minas Gerais, in Patrocínio, MG, Brazil. A randomized block experimental design was used with two replicates, spacing of 3.5 x 0.8 meters and ten plants per plot. The morphological characters were measured at 12 months after the plantation, at the plants juvenile phase. Only the first two major components explained 80.04% of total variance. Among the morphological evaluated traits, the length of the first plagiotropic branch, the plant vitality, the stem diameter and the nodes number of the first plagiotropic branch are the most important variables to discriminate the genotypes. These evaluations are important to the early selection of the genotypes of higher potential allowing to concentrate efforts in their evaluating, discarding other minor traits.